Relationship between the prevalence of Dibothriocephalus latus (Cestoda: Diphyllobothriidea) and the load of Escherichia coli: New findings in a neglected fish‐borne parasitic zoonosis. (6th September 2021) - Menconi, Vasco; Zoppi, Simona; Pastorino, Paolo; Di Blasio, Alessia; Tedeschi, Roberta; Pizzul, Elisabetta; Mugetti, Davide; Tomasoni, Mattia; Dondo, Alessandro; Prearo, Marino
Abstract: The sub‐Alpine lakes of Switzerland, Italy and France have long been reported as an endemic area of diphyllobothriosis, a parasitic zoonosis caused by Dibothriocephalus latus . With this study, we explored the hypothesis for a relationship between the prevalence of D. latus in Perca fluviatilis and the Escherichia coli load in lake water. To do this, we identified eleven sampling sites in three areas (north, centre and south) of Lake Iseo (north Italy) to determine E. coli load and the prevalence of D. latus in P. fluviatilis . Prevalence and 95% confidence interval (CI) of D. latus infestation ranged from 0% (95% CI: 0.71–0.0) in Sarnico (southern area) to 20% (95% CI: 33.0–11.2) in Pisogne (northern area). There were significant differences in prevalence between the sites (χ 2 = 31.12; p ‐value = .0006) and in E. coli load (Kruskal–Wallis test; p ‐value = .0005). There was decreasing gradient of E. coli load and prevalence of D. latus infestation from north to south. A significant positive correlation ( r = .881; p‐ value = .003) was found between E. coli load and prevalence of D. latus . Also, linear regression showed a significant relationship between E. coli load and prevalence of infestation ( R 2 = .775). Our findings offer an explanation for the link between E. coli load in water and D. latus prevalence. The potential factors in this link are the efficiency of the local wastewater treatment plant, the bathymetric profile of the lake and the life cycle of D. latus, which is mainly affected by light and water temperature.